Measuring and valuing travel time reliability – an example for hard shoulder operation - Vuren, Tom (Univerzita Pardubice, 2010)
Most transport infrastructure investments aim to reduce average travel times and their appraisal depends to a large extent on travel time savings and their value. There is an increasing recognition that in addition to average travel times, their reliability affects travelers’ choices and their valuation. However, the representation of travel time variability in network models, and hence our ability to forecast future impacts on reliability, has been limited. New data sources have enabled us to establish relationships between readily measurable characteristics and travel time variability. This now allows us to incorporate reliability in project appraisal, using standard economic cost-benefit techniques. The paper illustrates the method with an example of hard shoulder operations on Motorways around Birmingham in England.
Keywords: economic appraisal; travel time variability; hard shoulder operation